An arrangement of secretory cells involved in the formation and storage of resin in tracheid-based secondary xylem of arborescent plants - Tulik, Mirela; Jura-Morawiec, Joanna (Frontiers in Plant Science, 2023)
The evolution of the vascular system has led to the formation of conducting and supporting elements and those that are involved in the mechanisms of storage and defense against the influence of biotic and abiotic factors. In the case of the latter, the general evolutionary trend was probably related to a change in their arrangement, i.e. from cells scattered throughout the tissue to cells organized into ducts or cavities. These cells, regardless of whether they occur alone or in a cellular structure, are an important defense element of trees, having the ability to synthesize, among others, natural resins. In the tracheid-based secondary xylem of gymnosperms, the resin ducts, which consist of secretory cells, are of two types: axial, interspersed between the tracheids, and radial, carried in some rays. They are interconnected and form a continuous system. On the other hand, in the tracheid-based secondary xylem of monocotyledons, the resin-producing secretory cells do not form specialized structures. This review summarizes knowledge on the morpho-anatomical features of various types of resinreleasing secretory cells in relation to their: (i) location, (ii) origin, (iii) mechanism of formation, (iv) and ecological significance.